PERSEPSI MALL TERHADAP MOTIVASI KONSUMSI (STUDI KOMPARASI ANTARA IBU DAN PUTRINYA) - Pusporini, Pusporini; Aryani, Lina (Ekonomi dan Bisnis, 2014)
The purpose of this study was to examine whether adolescent consumers have different attitudes and perceptions about the mall when compared to her mother. And also to determine whether thedifferences in attitudes and perceptions influencing the encouragement/motivation in shoppingat a mall. Data were obtained from 100 pairs of mothers and their daughters. The data also includes information about the perceptions between mothers and daughters about the atmosphere in the mall and their motivation for shopping at the mall. The study was conducted in four malls in Depok. Mengidetifikasikan research results that mothers and their daughters are motivated to shop for different factors, and these factors have significant differences between the other related to their perception of the atmosphere in the mall. This study used a different test and regression analysis.